Faktor-Faktor Yang Berhubungan Dengan Keikutsertaan Wanita Usia Subur Dalam Pemeriksaan IVA di Puskesmas PAAL V Kota Jambi - Enny Susilawati; Nurmisih Nurmisih; Lia Artikasari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Cervical cancer is the second most common cancer that occurs in women and in developing countries including Indonesia. VIA examination is an alternative screening that has several benefits when compared to existing tests, namely effective (not much different from standard diagnostic tests), easier and cheaper. This study aims to analyze the factors related to the participation of WUS in the VIA examination at the Paal V Health Center, Jambi City. This type of research is analytic observational with cross sectional design. This research was conducted in September-December 2018 involving 81 WUS who visited the Paal V Health Center. The dependent variable in this study was the participation of women of childbearing age in the VIA examination while the independent variables were knowledge, attitudes, roles of officers and family support. Data analysis using chi square with a significance level of 95%. The results showed that there was a significant relationship between knowledge (0.223), attitude (0.081), officer role (0.745), family support (0.003).